THE APPROPRIATENESS OF THE SOCIAL MESSAGES IN MUZAFFER İZGÜ’S SOCIO-REALIST CHILDREN LITERATURE WORKS - Metin AKYÜZ (Fırat University, 2019)
Children and designs for the children have been followed by many ideologies with interest. Each ideology has attempted to shape the world of children in order to maintain its own future. Socio-realist sense of art was not indifferent to the children literature which is quite crucial for the foundation of the future world as well. The socio-realist sense of art, grounded on the messages about the social problems, presents works which include ideological thinking units into the literature. Muzaffer İzgü, an important figure of children literature, wrote some works in line with the socio-realism. His four novels (Kara Pamuk, Çizmeli Osman, Karlı Yollarda, Arıcık) created the scope of the study. In this study, these works were examined holistically and the social messages in the works were presented. During the analysis of the messages, repeated and featured meaning patterns and themes were determined. These were property, distance, sacrifice and organizing. İzgü presented the social problems within the frameworks of these themes. The interpretation of these messages is related to the making connections with the realities as the messages are shaped in a deep structure. However, the most important characteristics of children literature which distinguish it from the adult literature are the principles of children appropriateness emerging from the children realities. According to these principles, the messages in the children works can be presented in accordance with the cognitive and linguistic development of the children. It is impossible for the messages which are presented in this kind of meaning patterns and deep structure to reach children literature reader.